Optimalisasi Pembelajaran Fiqih dengan Model STAD di Madrasah Tsanawiyah: Implementasi Pragmatik untuk Menghadapi Tantangan Belajar Siswa - Ar, Fe Muhammad Muzahab Badar (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
This study was conducted with the aim of finding out the concept of pragmatism, and how a teacher behaves pragmatically to solve learning problems in students using the STAD learning model, especially in fiqh learning in Madrasah Tsanawiyah. The method used in this study is a literature study with the hope of obtaining suitable and relevant theories to support the arguments from the results of the research conducted. Then the next is the result of the research that has been carried out, including; Pragmatism comes from the word pragma (Greek) which means action, deed. Pragmatism is a school of philosophy that holds that the criterion of the truth of something is whether something has usefulness for real life. Learning problems are certain conditions experienced by students and hinder the smooth process carried out by individuals to obtain a new change in behavior as a whole. One way that can and is suitable to be used as a solution to learning problems is to use an interactive learning model, namely the Student Teams Achievement Division (STAD) learning model.